HEAT SUPPLY SYSTEM IMPROVEMENT OF CAMPUS AT UMAN NATIONAL UNIVERSITY OF HORTICULTURE - Golovchuk, A. F. (Science and Transport Progress, 2021)
Purpose. In modern conditions of energy consumption growth and a rapid increase in energy prices the actual problem is the development and implementation of energy efficiency programs and resource-saving conversion in to a source to provide the needs of industry and municipal power. The paper aims to solve the urgent problem of energy saving and efficient use of fuel-energy ones and heat supply system optimization on the basis of Uman National University of Horticulture (UNUH). Methodology. The work investigated the process of heating and hot water supply in the course of 2007-2015 years. Implementation of current problems of energy saving is grounded on the scientific-practical and efficient assurance of fuel and energy usage. At the same time energy-saving technologies are viewed as a priority direction of the energy sector development, reduction of man-induced impact on the environment and as a way of improving the competitiveness of the national economy. Findings. Statistical data acquisition and analyzing of gas flow and outside air temperature for nine years was carried out. On the basis of this analysis, the problem was identified and specific targets for its solutions were set. Originality. Scientific novelty lies in solving the problem of energy saving and efficient use of fuel resources in Ukraine through the use of a systematic approach, the methodology development of efficient use of different fuels and optimization of local heating operation, applying contemporary automation and control systems. Firstly it was in detail analyzed and conducted the comprehensive assessment of various factors influence on energy conservation. It takes into account the human factor, professionalism and responsibility of the operators of boilers and their superiors, as well as the relevant control services. Practical value. For UNUH campus hybrid use of solid fuel and gas boilers was carried out. Decentralization of the university heating system has been conducted through the restoration of 350 individual heating systems in residential buildings, remote departments and campus dormitories. The conclusions propose the list of activities upon the real economy of fuel and energy resources, and measures to overcome the economic and political crisis in the country.